'Gamification' for Health Behaviour Change in Smartphone Apps - Elizabeth Ann Edwards; Jim Lumsden; Carol Rivas; Lindsey Edwards; Hope Caton (Frontiers Media S.A., 2015)
Background: Gamification techniques are showing promise in promoting healthy behaviours and delivering health promotion advice, however, their use in Mobile-Health is relatively new. Gamification involves using 'gaming' elements such as badges, leader boards, health-related challenges, rewards, ability to 'level up' and use of avatars to motivate and engage people to change health behavior. Gamification techniques may also overlap with validated health behaviour change techniques (BCTs), however, few apps appear to apply the techniques systematically or to define the BCTs they include. Aim: We aimed a) to assess the number apps that incorporate gamification to modify health behaviors, b) to examine the BCT repertoire and combinations used in these apps c) to consider associations with user satisfaction. Methods: English-language health apps that contain gamification techniques were identified through a systematic search of the official Apple and Google Play store and the NHS health apps library. Top rated free and paid Medical, Health & Wellness, Health & Fitness apps as defined by Apple and Google Play stores were searched. Apps were coded for BCTs according to the Michie et al. taxonomy. The taxonomy comprises 16 categories and 93 individual BCTs. BCT coding was conducted by two trained researchers (EE, JL) who scored independently and then cross-checked for discrepancies. BCT numbers, user ratings and app pricing were compared. We explored the association between number of BCTs per app, user and NHS libraries' ratings and price. We also investigated, which of the 16 BCT categories and the individual 93 BCTs and their combinations were most commonly used. Results: 1,680 Medical, Health & Wellness or Health & Fitness Apps were reviewed and seventy containing gamification techniques were identified. The mean number of BCTs used was 12.5 (range 1-24). There was no correlation between number of BCTs, customer ratings, NHS library app rating or pricing. Commonly used BCT categories were: feedback & monitoring, reward & threat, goals & planning and comparison of behaviour. Commonly used individual BCTs were: self-monitoring of behaviour, non-specific reward, social support unspecified and non-specific incentive. Common combinations of BCTs were a) goal setting, self-monitoring and focus on past success b) goal setting, self-monitoring, non-specific reward and non-specific incentive. Only four apps were included in the NHS library. Conclusion: Our systematic review of smartphone health apps from two major providers suggests that gamification in Mobile-Health is relatively underused and there was wide variation in the use of BCTs. Whilst our data suggest that app designers are making some use of BCTs, as all apps contained at least one technique, many health apps underutilize them thus limiting the potential to modify health behaviour. In addition, there appears to be no correlation between what users rate as a good app (a possible proxy for the app having health benefits), and the app's content and potential ability to modify health behaviour. We suggest that app designers should work collaboratively with public health practitioners, health psychologists and with users to ensure that apps incorporate appropriate BCTs together with gamification in order to modify health behavior more effectively, to enhance user retention and to increase user enjoyment/ratings. Further research and clinical evaluation is needed for health care apps to evaluate their effectiveness in modifying actual health behavior and clinical outcomes. There is also a need for regulation of Health Care apps to ensure patients are given access to apps, which are safe and have proven benefit to health. Greater use of gamification and behavior change techniques could provide a potentially cost effective platform for health behaviour change and health promotion and have enormous Public Health impact.